Optimalisasi UMKM di Kepulauan Mentawai Melalui Marketplace dan Digitalisasi Logistik - Dwi Welly Sukma Nirad; Rika Ampuh Hadiguna; Ahmad Syafruddin Indrapriyatna; Wahyudi; Ricky Akbar; Hafizah Hanim; Andrew Kurniawan Vadreas (Journal of Applied Computer Science and Technology, 2023)
Economic growth in West Sumatra's Mentawai Islands is relatively undeveloped due to geographical conditions and human resource capacity. The status as a 3T region (Disadvantaged, Frontier, Outermost) inhibits Micro, Small, and Medium Enterprises (MSMEs) growth. Despite MSMEs being economic pillars that stimulate regional development, their progress remains slow. To counter this, our study proposes "Bulagat", an integrated marketplace with digital logistics aimed at enhancing economic and MSMEs growth in the Mentawai Islands. Bulagat will streamline MSME product distribution, broaden market reach, and boost income. Constructed using the Waterfall Model, Bulagat facilitates transactions between MSMEs and customers on an easy-to-use platform. The integration of logistics digitization aims to improve delivery safety and efficiency, thereby expanding MSMEs product reach in the Mentawai Islands. A tracking feature ensures successful delivery. The study suggests Bulagat has the potential to be an efficient tech solution supporting MSMEs product sales in Mentawai, overcoming geographical barriers, and strengthening the local economy and community welfare. This application aims to mitigate MSMEs challenges, drive economic growth, and enhance local community welfare.